Relief Shelter Design (Malaysia Flood- December 2013) - Abdullah, Che Zulkhairi; Abdul Rahim, Asiah; Zen, Ismawi; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; yussoff, nor'ain (2015)
The late December 2013 flood is a land tsunami that has largely affected Kelantan, Malaysia especially in place like Manek Urai. This is the first time in Malaysia history, where the flood level reached more than 100 feet in many places. Due to an unprecedented rise of sea level and monsoon rains, the amount of water that reach the villages and towns appears to behave like a wave. Malaysia follows the simple solution used by in many emergency situations, where large amount of tents was erected in many places after the water level goes down to a safe point. However, after a few weeks, this tent has been abandoned and being replaced by other than flood victims for many reasons that confused volunteers and government agencies. This research plan introduce to the Malaysian society, volunteer and charity group and government agencies to a better solution than a tent.